Perfil clínico e microbiológico de crianças em ventilação mecânica de uma unidade de terapia intensiva pediátrica - ALMONDES, Camila Maria Simas (2022)
Patients admitted to intensive care units (ICU) may have an increased amount of oral biofilm that is susceptible to colonization by respiratory pathogens. Recent studies that tried to relate microorganisms present in oral biofilm and respiratory pathogens found a high prevalence of respiratory bacteria in saliva and oral biofilm of adult patients hospitalized in ICU. In addition, unsatisfactory oral conditions can compromise the patient's systemic status favoring the development of nosocomial infections, such as ventilator-associated pneumonia, and impacting the increase in hospital stay. Thus, we aimed in chapter I to analyze the oral biofilm and tracheal aspirate of pediatric patients on invasive mechanical ventilation in order to observe the similarity of the microbiota and in chapter II, to describe the profile of patients assisted by the hospital dentistry service in an ICU and to investigate the association between the oral condition and the occurrence of ventilator-associated pneumonia (VAP) and others healthcare-associated infections (HAI). Chapter I is a retrospective descriptive study carried out with children admitted to the Pediatric Intensive Care Unit of the University Hospital of the Federal University of Maranhão - Maternal and Child Unit (HUUFMA-UMI) from March to December 2019. The sample consisted of 35 children on invasive mechanical ventilation via orotracheal tube. The oral biofilm was collected from the region of the dorsum of the tongue with a sterile swab and sent for culture examination with antibiotic susceptibility testing (AST). The collection was performed 48 hours after the patient was admitted to the ICU and always in the morning, before oral hygiene. Tracheal aspirate was collected after the collection of oral biofilm, following the routine of the pediatric ICU nursing team. It was found that in 34,3% of the participants the same bacterium was present in the lingual biofilm and in the tracheal aspirate, with Stenotrophomonas maltophilia and Acnetobacter baumannii being the most frequent. A statistically higher frequency of detection of the same species at both sites was observed in patients up to 24 months of age when compared to the older group (58,8% versus 11,1%, p = 0,004). The frequency of detection of the same species at both sites was higher among patients who died when compared to the group who were discharged from hospital (54,6% versus 25%, p = 0,087). There was a statistically higher frequency of deaths among patients up to 24 months of age (52,9% versus 11,1%, p = 0,01). There was a higher frequency of death among patients with mecanical ventilation duration greater than or equal to 10 days, but without significant differences (50% versus 15,8%, p = 0,065). It was concluded that there was a higher frequency of similarity of microorganisms in the two sites studied in patients up to 24 months of age and that this similarity was greater among patients who died. Thus, it is noted that the oral cavity of children hospitalized on invasive mechanical ventilation is a reservoir of respiratory pathogens. Chapter II, on the other hand, is a prospective descriptive study carried out with 143 children on mechanical ventilation who were hospitalized in the Pediatric Intensive Care Unit of the University Hospital of the Federal University of Maranhão - Maternal and Child Unit (HUUFMA-UMI) during the period of January 2019 to December 2020. Primary and secondary data were obtained from each participant, such as: sex, age, reason for hospitalization, length of stay, number of reintubations. The intraoral examination was performed at the bedside and information about the oral condition was the presence or absence of changes in teeth, gums and oral mucosa. After data collection, the patients continued to be monitored during the period they remained in the ICU, obtaining the evolution of each one: development of VAP and/or Other HAI and the outcome: discharge or death. The results showed that the majority were older than 24 months (46,15%) and had been hospitalized for up to 20 days (65,03%). Just over half had been under mechanical ventilation for more than 9 days (53,85%). During hospitalization, 19,58% of patients had VAP, 23,08% had other HAIs and 30,77% died. Most patients were in the deciduous dentition stage (43,36%) and 12,59% had lesions of the oral mucosa, mainly ulcerations. Both VAP patients and patients with other HAIs had longer hospital stays, ventilation time, and number of intubations than those who did not have these occurrences during hospitalization (p < 0,05). Oral mucosal changes were associated with a higher frequency of VAP after adjustment for confounding variables (adjusted OR = 3,94; 95%CI = 1,04-14,86; p = 0,042). It is concluded that the presence of skin lesions caused by pressure in the mouth is a reality in a pediatric ICU that may be associated with the development of VAP, due to the longer duration of mechanical ventilation. In addition, the importance of the oral hygiene protocol is emphasized as part of the care routine and the protocol to prevent the occurrence of pressure injuries in the oral mucosa.